Radiation balance and urban land use (case study: Kermanshah city) - taher Safarrad; mehran Mansourinia; hersh entezami (تحقیقات کاربردی علوم جغرافیایی)
Population growth and urbanization development are the main triggering factors of changes in urban land uses. These, in turn, result in changes in the components of radiation balance. The present study tries to analyze the role of urban land uses in radiation balance by calculating net radiation and its analysis. For this purpose, the Landsat 8 satellite image of 2016 was used. Characteristics of radiation flux including net radiation flux (RN), ground surface albedo (α), incoming longwave radiation (RL↓), incoming shortwave radiation (RS↓), outgoing longwave radiation (RL↑), and ground surface temperature were computed using Sebal algorithm.The values ​​of these components in different land uses (compressed residential, scattered residential, green area and wastelands) were analyzed using one-way analysis of variance (ANOVA) and Tukey’s test. The results of this study showed that the selected land uses have significant differences in the amount of radiation flux, therefore the wastelands are warmer than the residential areas by about 6 oC and the residential areas are warmer than the green areas by about 1.5 oC. The results also indicated that these differences are due to changes in output energy (α and RL↑), and any change in land use over time will ultimately lead to a change in the radiation balance and the temperature of those places, which this temperature increase, is different from the increase of the temperature due to global warming.